Tungstate fluorophosphate glasses as optical limiters - Poirier, G.; de Araujo, C. B.; Messaddeq, Younes [UNESP]; Ribeiro, SJL; Poulain, M. (American Institute of Physics (AIP), 2002)
Nonlinear absorption measurements were performed on fluorophosphate glasses with high concentrations of tungsten oxide. Large two-photon absorption coefficients, alpha(2), were determined at 660 nm using nanosecond laser pulses. It was observed that alpha(2) increases for increasing tungsten oxide concentrations and, hence, the optical limiting performance of this glass composition can be controlled. (C) 2002 American Institute of Physics.